2x -9x=3x+6 . x=      

10 Answers

pohnpei397's profile pic

pohnpei397 | College Teacher | (Level 3) Distinguished Educator

Posted on

First, subtract the numbers on the left side of the equation.  This gives you a result of -7x.  So now you have

-7x = 3x + 6

Now subtract 3x from both sides to get all the variables on one side.   That gives you

-10x = 6

So then you have to divide both sides by -10.  That gives you

x = -.6

You can verify that this is the correct answer by plugging this value for x back into the original equation.  You will end up with the equation 4.2 = 4.2 which is, of course, true.  This shows that x = -.6

malkaam's profile pic

malkaam | Student, Undergraduate | (Level 1) Valedictorian

Posted on

2x - 9x = 3x + 6


In order to solve this we need to isolate x.

2x - 9x = 3x + 6

-7x = 3x + 6

-7x - 3x = 3x + 6 - 3x            (subtract 3 from both sides)

-10x = 6

-10x/-10 = 6/-10                    (divide both sides by -10)

x = - 0.6 Answer

udonbutterfly's profile pic

udonbutterfly | Student, College Freshman | (Level 1) Valedictorian

Posted on

 2x -9x = 3x+6 

In order to solve for what x is you must put all the terms that are the alike on the same side

So you will have to add up the x's left side and you will get

-7x = 3x + 6 now you're going to add the -7x on both sides and then subtract the 6 on both sides.

(-7x) + 7x = (3x + 6) + 7x

(10x +6) -6 = (0) -6 You will get the -x by itself

10x = -6 Now divide 10 on both sides you will get  by itself.

(10x)/10 = (-6)/10

x= -6/10 = -3/5 = -0.60

zumba96's profile pic

zumba96 | Student, Grade 11 | (Level 3) Valedictorian

Posted on

First get all the Xs on one side

2x -9x=3x+6

Move the 3x to the other side


Combine like terms


Divide by -10 to get x

x=-6/10 or -.6

nisarg's profile pic

nisarg | Student, Grade 11 | (Level 1) Valedictorian

Posted on

2x -9x=3x+6

-7x=3x+6               simplify

-10x=6                   subtract 3x from both sides

x=-0.6                    divide both sides by -10

jess1999's profile pic

jess1999 | Student, Grade 9 | (Level 1) Valedictorian

Posted on

2x - 9x = 3x + 6

First combine the like terms on the left side of the equation ( 2x and -9x )

By combining the like terms your equation should look like

-7x = 3x + 6 now subtract 3x on both sides so "x" is on one side of the equation

By subtracting 3x on both sides, your equation should look like

-10x = 6  now divide -10 on both sides

by dividing, your equation should look like

x = -6/10 = -.6       which is your answer

nusratfarah's profile pic

nusratfarah | (Level 1) Valedictorian

Posted on

Bring the terms multipled by x together on the left hand side.


or, 2x-12x=6

or, -10x=6

or, 10x= -6 (both sides are divided by -1)

or, x= -(6/10) (both sides are divided by 10)

or, x= -0.6 (Ans.)

neela's profile pic

neela | High School Teacher | (Level 3) Valedictorian

Posted on

To solve 2x-9x = 3x+6.

Left side 2x and -9x are like terms. They could be simplified. and the result is: 2x-9x = -7x. Therefore, the given equation becomes:

-7x=3x+6. Take out 3x from both sides . This is done with a purpose of the unknown x's to be on one side konow their value in numbers on the  other side. So the equation now becomes:

-7x-3x = 3x+6-3x Or

(-7-3)x = 3x-3x+6 . The left side is written so by the distributive property and the right side  is by the associative and commutative property: As ax+bx = (a+b)x and  (a+b)+c= a+(b+c) = a+(c+b).

-10x = 6. Dividing by -10 both sides,

-10x/(-10) = 6/(-10) .

x= -(3/5) =-0.6, by rule of signs.


krishna-agrawala's profile pic

krishna-agrawala | College Teacher | (Level 3) Valedictorian

Posted on

The given equation is:

2x - 9x = 3x + 6

and we have to solve this equation for c

x, that is, to find out the value of x based on the equation.

The equation contains terms containing multiples of x and numbers. Such an equation is defined as a linear equation with a single variable (x).

The procedure to transfer all the terms containing multiples of x to left hand side of the equation to one side, and all the numbers on the other side.

The rule for shifting one side to the other is that the term remains same but with its sign reversed, that is +ve to -ve, and -ve to +ve.

Using these rules the equation can be simplified and solves in following steps:

2x - 9x = 3x + 6

2x - 9x - 3x = 6

10x = 6

dividing both sides of equation by 10 we get:

x = 6/10 = 0.6